Spatiotemporal dynamics of rhizosphere microbial communities under different mulching methods in spring maize - Wu, Jianlong; Chen, Kuo; Sheng, Lianghao; Han, Haoran; Li, Jiaxiu; Guo, Zhengyu; Gong, Shuai; Wang, Haoyu; Chen, Li; Zhang, Zhongdong; Gao, Fei (Frontiers in Plant Science, 2026)
IntroductionPlastic film mulching is a critical practice in arid agroecosystems, yet its spatiotemporal impacts on the rhizosphere microbiome remain poorly understood. MethodsHere, we investigated how no-mulching (CK), on-film hole sowing (UPM), and film-side planting (FPM) shape the bacterial and fungal communities in the maize rhizosphere across developmental stages (V12 and R6) and soil depths (10, 20, and 30 cm). ResultsConcurrently, both mulching strategies increased maize yield relative to CK, with FPM ultimately outperforming UPM (19.05% vs. 6.24%). Amplicon sequencing showed that mulching strongly structured the rhizosphere microbiome with clear spatiotemporal variation. Bacterial and fungal communities exhibited contrasting patterns: bacteria responded mainly in topsoil at V12 and across all depths by R6, whereas fungi responded across the soil profile at V12, with responses weakening with depth at R6. Mulching—particularly UPM—reduced key taxa, including the nitrifying genus Nitrospira and symbiotic Glomeromycota. Correlation analyses revealed significant associations between these taxonomic shifts and maize yield components, consistent with Nitrospira’s preference for aerobic conditions. Functional predictions suggested UPM favored communities with higher representation of anaerobic decomposition pathways, whereas FPM supported greater potential for aerobic heterotrophy and nitrogen-related processes.DiscussionAlthough microbial shifts were correlated with yield components, yield increases were likely dominated by the direct physical effects of mulching. Overall, distinct mulching strategies generated divergent rhizosphere trajectories, with FPM potentially offering a more sustainable option for dryland maize production.